The Effect of Psychiatric Consultations on Forensic Reports and Trial Process - Meral, Orhan; Ayaz, Nusret (The Bulletin of Legal Medicine, 2020)
Objective: The aim of this study was to draw attention to the importance of the effect on a forensic report of trauma-related mental health effects and their frequency revealed in psychiatric consultation requested by the Forensic Medicine Polyclinic for cases exposed to different kinds of trauma.Methods: A retrospective examination was made of 192 cases consulted by the Psychiatry Department for a report requested by the judicial authorities between June 2016 and September 2019. Psychiatric evaluation was made by psychiatry specialists according to the Diagnostic and Statistical Manual of Mental Disorders-V-TR (DSM-V-TR).Results: Evaluation was made of 192 cases comprising 54 (28.1%) males and 138 (71.9%) females with a mean age of 39.44±13.84 years. In 164 (85.4%) cases, the diagnostic criteria of a psychiatric disorder according to DSM-V-TR were met. Of these, although the physical effects of the trauma in 147 (89.6%) cases were classified as “of a nature which can be eliminated with a simple medical intervention”, the injuries of the mental effects were determined as “of a nature which cannot be eliminated with a simple medical intervention”. When the relationship between the event and gender was examined, 76.6% (n:118) of assault crimes were determined to have been perpetrated against females (p>0.005).Conclusion: In this study, findings of mental trauma were revealed, and consequently, the effect on the forensic report was determined. A multidisciplinary approach to trauma cases will provide more robust judicial management.
Keywords: Trauma, Forensic Report, Psychiatry, Consultation